Kur Syariah Microfinance Development Strategy (Case Study on Bank Syariah Indonesia KCP Sukabumi Sudirman) - Farida Herlina; Ma'mun Ma'mun; Eko Cahyadi (Interdisciplinary Social Studies, 2026)
This research aims to analyze and identify internal and external factors that are influential in the development of the microfinance portfolio. This research is a case study conducted by tracing data and information obtained from PT BSI, both at the center (MBG), Region VI Bandung, area and KCP Sukabumi Sudirman. The results of the total scores of the IFE and EFE matrix will be mapped with the IE matrix and then the formulation of strategies will be carried out to formulate the main strategy alternatives with the SWOT matrix and the QSPM matrix for better results. The results of the analysis with the IFE and EFE matrix were obtained that the dominant internal and external factors at BSI KCP Sukabumi Sudirman are cheap financing pricing with BSI People's Business Credit (KUR) products, easy requirements, Service Level Agreement (SLA) fast financing process, sharia financing contracts, microfinance promotion is still very lacking, restrictions on business segments that can be financed and coaching programs for business groups are still very lacking.  while the number of MSMEs in Sukabumi is very large, the public's interest in switching to Islamic banking is very high and competing banks that sell micro products are quite large. Based on the results of the SWOT analysis, it shows that alternative strategies that can be applied based on QSPM are building cooperation with micro business communities through micro-cluster financing, maximizing online marketing and services, innovating microfinance products to adapt to the development of community needs and improving the quality of human resources by consistently carrying out employee education and training.